Event-Related Brain Potential Investigation of Preparation for Speech Production in Late Bilinguals - Wu, Yan Jing; Thierry, Guillaume (Frontiers in Psychology, 2011)
It has been debated how bilinguals select the intended language and prevent interference from the unintended language when speaking. Here, we studied the nature of the mental representations accessed by late fluent bilinguals during a rhyming judgment task relying on covert speech production. We recorded event-related brain potentials in Chinese-English bilinguals and monolingual speakers of English while they indicated whether the names of pictures presented on a screen rhymed. Whether bilingual participants focussed on rhyming selectively in English or Chinese, we found a significant priming effect of language-specific sound repetition. Surprisingly, however, sound repetitions in Chinese elicited significant priming effects even when the rhyming task was performed in English. This cross-language priming effect was delayed by 200 ms as compared to the within-language effect and was asymmetric, since there was no priming effect of sound repetitions in English when participants were asked to make rhyming judgements in Chinese. These results demonstrate that second language production hinders, but does not seal off, activation of the first language, whereas native language production appears immune to competition from the second language.